If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(p+3)-5=-14-3p
We move all terms to the left:
-3(p+3)-5-(-14-3p)=0
We add all the numbers together, and all the variables
-3(p+3)-(-3p-14)-5=0
We multiply parentheses
-3p-(-3p-14)-9-5=0
We get rid of parentheses
-3p+3p+14-9-5=0
We add all the numbers together, and all the variables
=0
p=0/1
p=0
| 20+4=-4(4x-6) | | -46+23=46t+23 | | 3x+x+2=6x-2x=6 | | x+4+13x=18 | | 25(4x+9)=18 | | 2x-(-4x-9)=4 | | 4+5+980x=220 | | 8x-14+16x+5=39* | | 2(x+6)=2(12+x) | | 76=20x-4 | | 13(-16-11)-18f=161f-208 | | 8b-3=21 | | 11w-2w=8 | | 5(x-2)-6x=13 | | 2m-8=6m+8 | | 8x+10=8x+8-2x | | 5(3x+7)=-46+6 | | 2.3x+2.8=−1.2x+9.8 | | Y+7=10(x+10) | | -7/4=-7/4+2n/9 | | 34+x180=90 | | -9(x-2)+2=16-7x | | 19-5h=4 | | 2x-4=-2x+6 | | 7-3k=1-3k | | 2x+x+4=19 | | -46t-23=46t+23 | | x2=9/400 | | 2x+7=5x-3(x-4) | | 10+x/4=22 | | 1x/2-9=7.5+6x | | -24=-4(2x-4) |